Sustainable lithium-ion battery separators based on poly(3-Hydroxybutyrate-Co-Hydroxyvalerate) pristine and composite electrospun membranes - Barbosa, J. C. (2022)
To address the environmental issues related to lithium-ion batteries, environmentally friendlier separators based on poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) membranes are prepared by electrospinning. Cobalt ferrite (CFO) fillers can be incorporated to improve the electrochemical properties of the membranes and it is shown that fiber orientation and CFO filler addition have no relevant effect on the physicochemical properties of membranes. PHBV membranes show a well-defined porosity, resulting in liquid electrolyte retention above 300% by weight and an ionic conductivity at room temperature well above 1 mS cm−1, that depends on fiber orientation and filler addition. Battery separator performance is evaluated on half-cells demonstrating a discharge capacity value of about 130 mAh g−1 at C/5-rate with a relatively stable cycling behavior, independently of the electrospun membrane type. Composite membranes with oriented fibers show the best cycling behavior with 90 mAh g−1 at C/2-rate. The results confirm that the addition of CFO improves the battery performance of the PHBV membranes. The composite membranes based on natural polymers, still poorly explored alternatives to synthetic polymers for battery applications, show good cycling performance are demonstrated. The studied composite membranes are attractive candidates for the next generation of environmentally friendlier natural polymer-based separator membranes for lithium-ion battery applications.